INFLUENCE OF AROMATIC AMINO ACID DERIVATIVES ON THE LEVELS OF IMMUNE COMPLEXES UNDER IONIZED RADIATION - A. S. Boyajyan; S. A. Bajinyan; M. H. Malakyan; L. A. Manukyan; E. A. Arakelova; D. E. Yeghiazaryan (Медицинская иммунология, 2014)
Abstract. In the present study, blood levels of circulating immune complexes and of their pathogenic subpopulations were determined in rats following ionizing irradiation. Experimental animals were treated with synthetic Schiff base aromatic amino acid derivatives, nicotinyl-L-tyrosinate or nicotinyl-L-tryptophanate, before irradiation, whereas untreated irradiated rats served as controls. The results obtained demonstrate significantly increased levels of immune complexes, as well as presence of a pathogenic subpopulation of circulating immune complexes in blood of irradiated animals. In addition, the data obtained suggest a normalizing effect of nicotinyl-L-tyrosinate and nicotinyl-L-tryptophanate upon the mentioned parameters. On the basis of these observations, a cyto- and immunoprotective ability of nicotinyl-L-tyrosinate and nicotinyl-L-tryptophanate may be proposed.